THE RELATIONSHIP BETWEEN THE INTENSITY OF ISLAMIC SPIRITUAL GUIDANCE AND THE LEVEL OF ANXIETY IN INPATIENTS AT SARI ASIH HOSPITAL, CILEDUG - Nur Solichatik; Dyah Wiji Puspita Sari; Retno Issroviatiningrum (The Shine Cahaya Dunia D-III Keperawatan, 2026)
Background; Anxiety often appears and is considered as response to a number of perceived threat . Suboptimal spiritual guidance and low spiritual understanding will influential to ability patient use positive coping . Research previously mention that part big patient care stay own level anxiety moderate . And spiritual guidance Islam have influence as big as to level anxiety patient care stay overnight . So from that , research This aim For know connection intensity guidance spiritual Islam with level anxiety patient care stay , with hope can give useful insights and knowledge for practice nursing and management anxiety patient. Method; Study This use approach quantitative , type analytic correlation with cross sectional design , with amount respondent 132. Technique taking sample using purposive sampling. Criteria inclusion is patients treated in the room mature rpu lt.2 and religious Islam . Criteria exclusion study This is patients who do not conscious and patient non-Muslims . Data collection using LIKERT and HARS (Hamilton Anxiety Rating Scale) questionnaires Result; Univariate test results of the total respondents 132, the intensity guidance spiritual Islam with category currently as many as 62 respondents (47.0 %) and the level anxiety patient part big respondents No experience anxiety namely 80 respondents ( 60.6%). Respondents with group ages 41 to 60 years most namely 82 respondents (62.1%) and Gender Woman as many as 72 respondents (54.5%). Spearman correlation test obtained p- value 0.000 and r correlation -0.615. Conclusion; There is a strong relationship between variables intensity guidance spiritual Islam with level anxiety patient care hospitalization . Research furthermore expected Can use location study with a larger area broad , so that the results obtained are also more general